In via veritas : route as a paradigm for urbanism - Bruyn, Joeri de; van Acker, Maarten; Buyse, Filip; Rasier, Frédéric; Vanden Abeele, Peter (Mechelen : Public Space, 2014)
The concept of via/route allows us to contemplate architecture and city planning in a different way. The route offers a new way to read territory. It reveals spatial and temporal connections that had not previously been visible. Elements that today appear separate in space and time prove to have coherent connections, exerting a mutual and fundamental influence on each other. The new perspective leads to a new approach to planning. The classical practice of planning sets things in stone, defines destinations and forms, aims to achieve comprehensive completion. Designing with routes as a tool does not result in crystallization of the space, but is a process en route, the establishment of a potential. Routes are also processes. 'In via veritas' means that truth is discovered along the route.
Deze uitgave verschijnt ook in het Nederlands onder de titel In Via Veritas. Route als paradigma voor ruimtelijk ontwerp
boek